Arthropod functional traits shaped by landscape-scale field size, local agri-environment schemes and edge effects - Gallé, Róbert; Geppert, Costanza; Földesi, Rita; Tscharntke, Teja; Batáry, Péter (Basic and applied ecology, 2020)
Agri-environment scheme (AES) approaches can be classified according to whether they prescribe management in non-productive areas, such as field boundaries and wildflower strips, or in productive areas, such as arable crops. Here we tested the ecological effectiveness of two popular AESs in Germany: wildflower strips next to winter wheat fields as off-field management and organic farming on winter wheat fields as on-field management. We selected ten landscapes along a field size gradient with three focal wheat fields, one conventional field with flower strip, one organic field and one conventional field without flower strip as a control. We sampled arthropods with pitfall traps at field edges and field interiors. We selected three ecological traits for spiders and carabids (body size, feeding trait, dispersal ability). We calculated community weighted mean values (CWM), and we used linear mixed effects models to test the effect of management type and transect position on CWM values. We found pronounced edge effects on most traits, and weaker effects of field size and AES in shaping functional traits. Smaller spiders, spiders with higher ballooning propensity and more web-builders were in the field interior than at the field edge, whereas carnivore carabids preferred field interiors. We also found a strong effect of landscape configuration, i.e. mean field size, as larger field size was positively related to more web-building spiders and more carnivore beetles. Flower strips enhanced populations of web-building spiders. Our results suggest that small-scale agriculture leading to high landscape-scale edge density has a major effect in shaping functional traits and potential ecosystems services in agricultural landscapes. Spider and carabid communities exhibit very different responses to edge vs. interior sites, and, based on the landscape-scale field size gradient emphasize the importance of landscape configuration in shaping the heterogeneity of the arthropods’ traits and presumably ecosystem services in agricultural landscapes.